(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
This paper reports for the fist time in Colombia the jellyfih Lychnorhiza sp., aff. L. lucerna, based on seventeen individuals collected in front of Isla de Rosario (Magdalena). This jellyfih is one of the most common inhabitants in coastal waters from southeastern Brazil to northern Argentina, but it was not recorded yet from the Caribbean coast of Colombia.